A History of the Newfoundland Federation of Labour, 1936-1963 - Gillespie, Bill (Memorial University, 1980)
Throughout its history the Newfoundland Federation of Labour has pursued two primary goals - to spread trade union organization and to lobby government to adopt legislation favourable to the interests of working people. The degree to which the Federation has been successful has depended upon the quality and dedication of its leadership, economic conditions and the willingness of government to be influenced. An unstable, rural economy delayed the emergence of a Newfoundland Labour Movement until the mid-1930s. Once it did emerge, however, Newfoundland workers responded enthusiastically. The NFL's founding meeting in 1937 at Grand Falls was followed by a country-wide organizing drive. Despite a six year lull caused by World War II, by the late 1940s the Newfoundland labour force was the most highly operated in North America. Unlike their counterparts in Britain, however, Newfoundland trade unionists were unable to translate their numerical strength into political power. The explanation lies in a combination of the NFL's relationship to sections of the North American Labour Movement opposed to direct political action, divisions within the Newfoundland Labour Movement, and a set of political circumstances unique to Newfoundland. – Although the NFL was a national labour central until Confederation with Canada in 1949, it was dominated by unions affiliated to the American Federation of Labour. The AFL's opposition to direct political action is well documented. However, in a country with strong ties to Great Britain the success of the British Labour Party provided an alternate model. Even so, there were only two serious attempts between 1937 and 1963 to emulate British practice. For the most part the NFL was less "political" than even the AFL. Initially this was because from 1933 to 1949 Newfoundland was governed by a commission of civil servants appointed by Britain. In a country without a system of electoral politics, direct political action did not seem a pressing concern. When electoral politics were restored and J.R. Smallwood became premier of Canada's tenth province, Smallwood granted the NFL almost every request it made for legislative reform. As a result the NFL saw no need to develop an independent political base in order to guarantee its influence with government. The fault with this approach was demonstrated during the IWA Strike of 1959. Smallwood suddenly turned against the Federation and without a political base of its own the NFL was powerless to protect the interests of Labour. Smallwood's subsequent attacks on the NFL sent it into a ten year period of decline; however, it is the thesis of this dissertation that the NFL's failure to give sufficient weight to the changed environment brought about by the return to electoral politics was as much the cause of its decline as any external factor.